Thermodynamics of the substantial universe - V. Yu. Stetsenko (Литьë и металлургия, 2024)
Based on thermodynamic calculations of the substantial Universe, it is shown that the cosmological theory of the Big Bang is erroneous. The thermodynamic ban on this theory makes the hypothesis of dark energy expanding the substantial Universe also erroneous. It is shown that the substantial Universe is a thermodynamically equilibrium system. Therefore, the substantial Universe cannot disintegrate, losing its structure, cannot shrink to a point, cannot disappear into a black hole. The equilibrium substantial Universe exists forever, preserving its enthalpy, entropy, mass and temperature. The main reason for the redshift of spectral lines of light from distant stars and galaxies is not the expansion of the substantial Universe, but its clouds of gas and dust, which reduce the energy of photons.